Social and racial inequalities in preterm births in Western Australia, 1984 to 2006 - Langridge, A.; Nassar, N.; Li, Jianghong; Stanley, F. (Blackwell Scientific Publications, 2010)
Social and racial inequalities in preterm births in Western Australia, 1984 to 2006 1. Amanda T. Langridge1,*, 2. Natasha Nassar1, 3. Jianghong Li2, 4. Fiona J. Stanley1Article first published online: 21 MAY 2010DOI: 10.1111/j.1365-3016.2010.01124.x© 2010 Blackwell Publishing Ltd.IssuePaediatric and Perinatal EpidemiologyPaediatric and Perinatal EpidemiologyVolume 24, Issue 4, pages 352–362, July 2010Additional Information(Show All)How to CiteAuthor InformationPublication HistoryHow to CiteLangridge, A. T., Nassar, N., Li, J. and Stanley, F. J. (2010), Social and racial inequalities in preterm births in Western Australia, 1984 to 2006. Paediatric and Perinatal Epidemiology, 24: 352–362. doi: 10.1111/j.1365-3016.2010.01124.xAuthor Information 1. 1 Telethon Institute for Child Health Research, Centre for Child Health Research, University of Western Australia, and 2. 2 Curtin Health Innovation Research Institute, Centre for Developmental Health, Curtin University of Technology, Perth, Australia*Correspondence: Amanda T. Langridge,*Correspondence: Dr Amanda Langridge, Telethon Institute for Child Health Research, PO Box 855, West Perth, WA 6872, Australia. E-mail: amandal@ichr.uwa.edu.auPublication History 1. Issue published online: 1 JUN 2010 2. Article first published online: 21 MAY 2010SEARCHSearch ScopeSearch String * Advanced > * Saved Searches >SEARCH BY CITATIONVolume:Issue:Page:ARTICLE TOOLS * Get PDF (363K) * Save to My Profile * E-mail Link to this Article * Export Citation for this Article * Get Citation Alerts * Request Permissions * Abstract * Article * References * Cited ByView Full Article (HTML) Get PDF (363K)Keywords: * preterm delivery; * socio-economic factors; * time trends; * Aboriginal population; * neighbourhood deprivationSummaryLangridge AT, Nassar N, Li J, Stanley FJ. Social and racial inequalities in preterm births in Western Australia, 1984 to 2006. Paediatric and Perinatal Epidemiology 2010.Preterm birth is associated with a range of childhood morbidities and in industrialised societies is the primary cause of infant mortality. Social and racial inequalities in preterm birth have been reported in North America, UK, Europe and New Zealand. This study utilised population-level data to investigate social and racial inequalities in preterm birth among Aboriginal and non-Aboriginal infants in Western Australia. All live, singleton births between 1984 and 2006 (n = 567 468) were included, and multilevel multivariable logistic regression was used to investigate relative differences in preterm infants between socio-economic groups. Aboriginal and non-Aboriginal infants were analysed separately.The prevalence of preterm births increased from 7.1% in 1984–88 to 7.5% in 1999–2003, before decreasing to 7.2% in 2004–06. Inequalities in preterm births between Aboriginal and non-Aboriginal infants increased over time, with the percentage of preterm births being almost twofold higher for Aboriginal infants (14.8%), compared with non-Aboriginal infants (7.6%). A significant portion of the disparity between Aboriginal and non-Aboriginal infants is attributable to parental socio-economic and demographic characteristics, though the disparity continues to persist even after adjustment for these factors. While the overall rates of preterm birth in Western Australia have remained fairly static over the last two decades, the disparity between Aboriginal and non-Aboriginal infants has increased and is now similar to inequalities seen 20 years ago. These findings highlight a major public health issue that should be of great concern, given the short- and long-term morbidities and complications associated with preterm birth.View Full Article (HTML) Get PDF (363K)More content like thisFind more content: * like this articleFind more content written by: * Amanda T. Langridge * Natasha Nassar * Jianghong Li * Fiona J. Stanley * All Authors * ABOUT US * HELP * CONTACT US * AGENTS * ADVERTISERS * MEDIA * PRIVACY * TERMS & CONDITIONS * SITE MAPCopyright © 1999-2010 John Wiley & Sons, Inc. All Rights Reserved.